Sliding induced multiple polarization states in two-dimensional ferroelectrics - Peng Meng; Yaze Wu; Renji Bian; Er Pan; Biao Dong; Xiaoxu Zhao; Jiangang Chen; Lishu Wu; Yuqi Sun; Qundong Fu; Qing Liu; Dong Shi; et al. (Nature Communications, 2022)
Layer dependence is an important aspect to properties of van der Waals materials. Here, the authors obtain layer dependent multiple polarization states in 3 R MoS2 and propose a generalized model to describe their ferroelectric switching processes.